2020
DOI: 10.1111/bjh.16449
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of 2CdA (cladribine) in extra‐pulmonary adult‐onset Langerhans cell histiocytosis: analysis of 23 cases from the French Histiocytosis Group and systematic literature review

Abstract: Summary Langerhans cell histiocytosis (LCH) is a rare protean disease that usually affects children. Few data are available for management of adult‐onset cases. A complete picture of the efficacy and safety of 2CdA (2‐chlorodeoxyadenosine, cladribine) is lacking. We report a retrospective multicentre study of 23 adult LCH (a‐LCH) patients who received single‐agent 2CdA and a systematic literature review. All had previously received systemic therapy (vinblastine, n = 19). Response to 2CdA was evaluable in 22 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
9
1
4
Order By: Relevance
“…In a recent review of published cases of cladribine treatment, the patients who had a PR were found to be at a higher risk of relapse than those who had a CR. 6 However, our data did not reveal any differences in PFS based on the depth of response. Responses were seen irrespective of disease sites and BRAF-V600E status; however, there was a trend toward better PFS and OS in BRAF-V600-wt patients, likely statistically insignificant because of small sample size.…”
Section: Single-agent Cladribine As An Effective Front-line Therapy F...contrasting
confidence: 74%
See 1 more Smart Citation
“…In a recent review of published cases of cladribine treatment, the patients who had a PR were found to be at a higher risk of relapse than those who had a CR. 6 However, our data did not reveal any differences in PFS based on the depth of response. Responses were seen irrespective of disease sites and BRAF-V600E status; however, there was a trend toward better PFS and OS in BRAF-V600-wt patients, likely statistically insignificant because of small sample size.…”
Section: Single-agent Cladribine As An Effective Front-line Therapy F...contrasting
confidence: 74%
“…A recent retrospective case series of 23 adults with relapsed/refractory LCH revealed an impressive ORR of 91%, but did not include any patients treated in frontline with the drug. 6 There is a lack of contemporary studies examining the efficacy of cladribine in the front-line systemic treatment of adult LCH. Moreover, with the advent of targeted BRAF-inhibitors in histiocytic neoplasms, the role of cladribine in the context of BRAF-V600E mutation status is unknown.…”
Section: Single-agent Cladribine As An Effective Front-line Therapy F...mentioning
confidence: 99%
“…Langerhans cell histiocytosis (LCH) is a myeloid neoplasm with inflammatory properties [1] . It most often affects the bones in children, with a peak between the age of 1 and 4 years old [2 , 3] . LCH can affect single (unifocal) or multiple organs of the human body (systemic) [4 , 5] .…”
Section: Introductionmentioning
confidence: 99%
“…In this cohort, treatment was based on the national paediatric LCH recommendations, which consisted of six courses of 2CDA. However, the optimal number of 2CDA courses remains unclear, because in other studies, on adults with LCH, treatment consisted of four courses of 2CDA 29 . Additionally, the utility of maintenance therapy must be explored further in a randomized trial for cases of stable disease or partial response at the end of 2CDA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal number of 2CDA courses remains unclear, because in other studies, on adults with LCH, treatment consisted of four courses of 2CDA. 29 Additionally, the utility of maintenance therapy must be explored further in a randomized trial for cases of stable disease or partial response at the end of 2CDA therapy. Future studies should investigate how to better define early disease remission to guide decisions about therapy adaptations, because lesions can appear stable for prolonged periods, despite the response to intralesional therapy.…”
Section: Discussionmentioning
confidence: 99%